2019
DOI: 10.9734/jcti/2019/v9i230105
|View full text |Cite
|
Sign up to set email alerts
|

Proportions of Pre-Cancerous Cervical Lesions and Its Associated Factors among Women Clients in the Age Group of 30-49yrs in Gynecology Ward of Dessie Referral Hospital and FGAE, North-East Ethiopia, 2016

Abstract: Introduction: Globally, cervical cancer is the second most common cancer in women; in 2008 there were an estimated 530,000 new cases and more than 270,000 women die from it [1]. In Ethiopia, cervical cancer is the second most common cancer following breast cancer and the leading cause of death from cancer. Annually, an estimated number of 4648 women develop the cancer and 3,235 die from it. Low-resource countries experience 85% of the global burden and in regions such as Eastern Africa and South-Central Asia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 5 publications
5
8
1
Order By: Relevance
“…Moreover, our findings are also in line with other studies. 15 , 25 , 32 , 37 , 41 , 43 Having multiple sexual partners increases the likelihood of acquiring HPV infection and in turn cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our findings are also in line with other studies. 15 , 25 , 32 , 37 , 41 , 43 Having multiple sexual partners increases the likelihood of acquiring HPV infection and in turn cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected using a pretested structured questionnaire prepared by reviewing related studies, with modifications in line with the objectives of this particular study. 12 , 15–17 Two days of training on data-collection procedures was given for data collectors. Six BSc-qualified nurses certified in cervical screening and working in the gynecology ward in selected hospitals were assigned to collect the data, and the principal investigator supervised data collection.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, we used a DerSimonian and Laird random effects model [ 48 , 49 ] to estimate the pooled prevalence of precancerous cervical lesion. Studies that showed the largest weight were Plezer et al [ 37 ] that showed 6.35, Kebede et al [ 34 ] with 6.11, Temesgen et al [ 42 ] with 6.10, and Belayneh et al [ 28 ] that showed 6.80 weight, whereas Birara et al showed a relatively smaller weight which was 5.62 (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were included from the Southern Nations Nationalities and People Region (SNNPR) [ 30 , 32 , 38 , 39 , 41 ]. In addition, five studies were included from the Amhara region [ 27 , 28 , 31 , 33 , 42 ]. The remaining two articles were from Oromia [ 43 ] and Tigray [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Ethiopia, different studies were conducted to determine the prevalence and factors associated with precancerous lesions of the cervix. These studies reported that the prevalence of precancerous lesions among women ranges from 6.7% to 27.7% [ 10 21 ]. The common factors reported by the studies were early initiations of first sexual intercourse, multiple sexual partners, and a history of STI [ 11 , 12 , 14 , 16 , 17 , 19 – 23 ].…”
Section: Introductionmentioning
confidence: 99%